A visual guide to scleroderma and approach to treatment - Mayes, Maureen D. (Springer New York, 2014)
A Visual Guide to Scleroderma and Approach to Treatment offers a focused analysis of the diagnosis and management of scleroderma.  Specifically designed to enlighten and update students and trainees, practicing rheumatologists, and general practitioners on the various forms of systemic sclerosis, the book is designed to be an easily accessible tool that also covers potential complications and the latest treatment developments.  A Visual Guide to Scleroderma and Approach to Treatment emphasizes recognition of common clinical features by focusing on and illustrating severe and less severe forms of the disease that can involve internal organs such as the gastrointestinal tract, heart, lungs, and kidneys. Photos and radiographs introduce each chapter and are accompanied by a guide to workup and treatment. A comprehensive and invaluable addition to the literature, this text is not only a necessary resource for students, trainees and primary care physicians; it will also be of significant interest to specialists in the fields of rheumatology, dermatology, pulmonology, cardiology, gastroenterology, and nephrology.